Soil radioactivity and elemental characterization of area proposed for the first nuclear power plant at Red Sea state, eastern Sudan - Abdoun, Nessreen Abdelfatah Ali (Open Science Journal, 2020)
Abstract This work was carried out with the aim to establish baseline data of soil radioactivity prior commissioning the first nuclear power plant for electricity production in the Sudan. A total of 105 soil samples from the proposed area were collected and analyzed using Gamma-ray spectrometer, X-ray Fluorescence and Atomic Absorption. Ambient dose rates were measured during sampling using radiation survey meters. Based on radionuclides in soil; some radiological hazard indices (such as absorbed dose rates, Radium-Equivalent Activity, External Hazard, and Gamma index) were computed. The results exhibit that226Ra, 232Th,40Kand 137Cs concentration ranged from0.55-88.9, 1.63-76.6, 24-1100 and 0.001-1.03 Bq/kg with an average value of10.43, 11.12, 361.2and 0.045Bq/kg respectively. The average value of absorbed dose rate(29.92nGy/h), Radium equivalent (70.55 Bq/Kg), external hazard (0.19), Gamma index. (0.25) and those parameters are lower than the corresponding global average. The results of the study revealed that the average values of 226Ra, 232Th, 40K and 137Cs fall within the global average value. GIS Predictive exhibited the spatial distribution of radioactivity trends with low levels at eastern part towards the Red Sea while high values observed at the desert (western part). This trend in addition to low levels has a very good impact to decision makers for consideration in site selection of NPP. Pearson correlation coefficient shows a correlation between the variables 226Ra and 232Th (0.69); Cr and Au (0.82); Br and Nb (0.84),Hf and Sb (+0.75) with no significant correlations between radioactive and radioactive elements. Keywords: Road map, GIS, Gamma-ray Spectrometer, Effective dose.